ChemInform Abstract: Design, Synthesis, Docking Study and Biological Evaluation of Some Novel Tetrahydrochromeno [3′, 4′:5, 6]Pyrano[2, 3‐b]quinolin‐6(7H)‐one Derivatives Against Acetyl‐ and Butyrylcholinesterase. Issue 12 (25th March 2014) - Khoobi, Mehdi; Alipour, Masoumeh; Moradi, Alireza; Sakhteman, Amirhossein; Nadri, Hamid; Razavi, Seyyede Faeze; Ghandi, Mehdi; Foroumadi, Alireza; Shafiee, Abbas
Abstract 18 Title compounds of type (III) are prepared and evaluated for their AChE and BuChE inhibitory activities.